(untitled) (Revista Argentina de Musicología, 2019)
The three works that under the title of Pampeanas composes Alberto Ginastera are contemporary with the philosophical reflections of Carlos Astrada that thematize that landscape, determining the constitution of the gaucho myth and its projection in Argentine history until the middle of the twentieth century. Both disciplinary fields, music and philosophy, appeal to different conceptual and sensitive tools to refer to that geography. Through them emerge different temporalities, superimposed, manifested in theoretical frameworks, musical material and compositional techniques of different historical depth, whose ideological and aesthetic repercussions in the cultural and political context of the time the present article analyzes. Also explored are the relationships between historicity and myth: between the thinking and representation of the Pampa within the continuing traditions of the nineteenth century and contemporaneity—both in the field of production and in the metaphors employed to refer to it.